MANAJEMEN EVALUASI PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN KETERAMPILAN HIDUP GURU DI SEKOLAH DASAR DENGAN MENGGUNAKAN MODEL KIRKPATRICK - Tiara Amalia; Roihan Sadad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of a women's empowerment program through life skills training at the elementary school level using the Kirkpatrick Evaluation Model. The main objective is to assess the extent to which the training impacts participants’ knowledge, attitudes, and behaviors, as well as its contribution to improving the quality of life of women, particularly in social and economic aspects.This research adopts a descriptive qualitative approach with purposive sampling techniques. Data were collected through in-depth interviews, direct observations, and document analysis involving ten participants from a local women’s empowerment organization. The evaluation was conducted based on the four levels of the Kirkpatrick Model: reaction, learning, behavior, and results.The findings indicate that participants responded positively to the training materials, delivery methods, and facilities (reaction). They showed improved understanding and skills in entrepreneurship and household management (learning) and were able to apply these skills in their daily lives (behavior). At the results level, the training had a positive impact on participants’ self-confidence, social roles, and economic participation.This study contributes to the context of basic education by highlighting the importance of involving women in the planning and evaluation of empowerment programs to ensure they are more effective, relevant, and sustainable.